(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Existing studiesreveals that the huge surge in international capital flows since early 1990shas created unprecedented opportunities for the developing countries like Indiato achieve accelerated economic growth. International financial institutions routinely advise developingcountries to adopt policy regimes that encourage capital inflows. Since the introductionof the reform process in the early 1990s, India has witnessed a significantincrease in capital inflows. The size of net capital inflows to India increasedfrom US 7.1 billion in 1990-91 to US 108.0 billion in 2007-08. Today, Indiahas one of the highest net capital inflows among the EMEs of Asia. Capitalinflows, however, not an unmitigated blessing. The main danger posed by largeand volatile capital inflows is that they may destabilize macroeconomicmanagement. As evident, the intensified pressures due to large and volatile capitalflows in India in the recent period in an atmosphere of global uncertaintieshas posed new challenges for monetary and exchange rate management. The presentpaper elaborates on various aspects of the capital inflows to India and theirpolicy implications.